The fear of exclusion: Individual effort when group formation is endogenous - Kjell Arne Brekke; Karine Nyborg; Mari Rege (University of Oslo, Department of Economics, 2005)
To secure their membership in a popular group, individuals may contribute more to the group's local public good than they would if group formation were exogenous. Those in the most unpopular group do not have this incentive to contribute to their group. Substantial differences in individual efforts levels between groups may be the result. A principal may prefer either exogenous or endogenous group formation, depending on whether an increase in contributions to the local public good coincides with the principal's interests. We analyze two examples: Social interaction in schools, and multiple-task teamwork.
Keywords: C72; D11; D23; L24; Z13; 330; Local public goods; opportunity costs; popularity; multiple-task principalagent analysis; Soziale Isolation; Lokales öffentliches Gut; Opportunitätskosten; Prinzipal-Agent-Theorie; Soziale Gruppe